2006
DOI: 10.1093/nass/nrl052
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric allele analysis based on the DNA-directed cooperative formation of luminous lanthanide complexes

Abstract: We present the facile technique of colorimetric SNP analysis through DNA-templated cooperative complexation between a luminescent lanthanide ion (Ln(3+): Tb(3+) or Eu(3+)) and two ODN (oligodeoxyribonucleotide) conjugates carrying a metal chelator. Ethylenediaminetetraacetic acid (EDTA) and 1,10-phenanthrorine (phen) were covalently attached to ODNs to form the conjugate probes, capture and sensitizer probes, respectively. The sequences of the conjugates were designed so as to form a tandem duplex with a targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Using this novel design of the multicomponent DNAzyme-based sensor system, authors were able to detect various viral, bacterial, cellular DNA and RNA. ) attached to allele-specific capture probes was demonstrated to be a useful tool in colorimetric SNP sensing of G/C mismatch in the thiopurine S-methyltransferase (TPMT) gene [60]. In doing this, 7mer capture probes, Cwt7 and Cmut7, complementary to wild-type and the mutant part of the target gene, respectively, and carrying EDTA at the 5' terminus, were prepared.…”
Section: Other Optical Methods For Sensing Snpmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this novel design of the multicomponent DNAzyme-based sensor system, authors were able to detect various viral, bacterial, cellular DNA and RNA. ) attached to allele-specific capture probes was demonstrated to be a useful tool in colorimetric SNP sensing of G/C mismatch in the thiopurine S-methyltransferase (TPMT) gene [60]. In doing this, 7mer capture probes, Cwt7 and Cmut7, complementary to wild-type and the mutant part of the target gene, respectively, and carrying EDTA at the 5' terminus, were prepared.…”
Section: Other Optical Methods For Sensing Snpmentioning
confidence: 99%
“…As illustrated below, several non-enzymatic techniques provide advantages of improved repeatability, decreased cost and robustness. Based on the chemical nature of the utilized probe, these techniques can be divided into three groups: methods applying nano-and magnetic-particles , (1) aptamer-and protein-based assays [47][48][49][50][51][52], (2) and other techniques utilizing bright chemically modified nucleic acid analogues [53][54][55][56][57][58][59][60]…”
Section: Toward Enzyme-free Detection Of Snpmentioning
confidence: 99%
“…Some organic molecules, silver and gold oxide nanoparticles were applied to detect Co 2+ [26][27][28][29][30], and a lanthanide show sensing effect to Zn 2+ , Cd 2+ and Co 2+ at the same time, but it is not a selective Co 2+ sensor [27]. That is, though lanthanide complex had been reported to detect many kinds of ions and molecules [1,3,[31][32][33][34][35][36][37][38][39][40], due to its unique photophysical properties (such as microsecond to millisecond lifetimes, characteristic and narrow emission bands, as well as large Stokes shifts), the selective sensing to Co 2+ is not reported. Therefore, selective and sensitive sensing Co 2+ by luminescent lanthanide complex is urgent and interesting.…”
Section: Introductionmentioning
confidence: 99%
“…That is, it provides more quality signals than that expected from the system focusing on a one-onone interaction between the targets and probes. In these several years, we have been engaged in the development of gene detection with a smart manner through the cooperative action between the probes [13,23,[34][35][36][37][38][39]. In a series of studies, we showed that the hybridization of ODN (oligodeoxyribonucleotide) conjugates 0162-0134/$ -see front matter Ó 2008 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…doi:10.1016/j.jinorgbio.2008.06.016 bearing a metal chelator on their terminus was efficiently controlled by a metal ion as an allosteric effector. This work suggested that the general concept of ''metal ion-directed cooperative recognition" could be applied to the split-probing of specific genes by employing luminescent lanthanides as the metal ion [34][35][36][37]. Metal-centered luminescence from the complexes of the trivalent lanthanide ions (Ln(III)) have been widely exploited in bioassays.…”
Section: Introductionmentioning
confidence: 99%